Reproductive outcomes of lactating dairy cows submitted to first timed artificial insemination protocols with different strategies to induce final ovulation - Carlos E.C. Consentini; Leonardo F. Melo; Jessica C. Lemos Motta; Lucas Oliveira e Silva; Natália Picoli Folchini; Rodrigo L.O.R. Alves; Guilherme Madureira; Tiago Oliveira Carneiro; Tattiany Abadia; Luis Moroz; Robson V.S. Fortes; Sergio Soriano; et al. (Journal of Dairy Science)
ABSTRACT: The study evaluated strategies for induction of ovulation at the end of timed AI (TAI) protocols initiated after a novel presynchronization strategy. A total of 909 lactating dairy cows from 6 dairy herds initiated a presynchronization protocol on d −15 with an intravaginal progesterone (P4) implant and 7 d later (d −8) were treated with 1.0 mg of estradiol cypionate (EC) and 0.530 mg of cloprostenol sodium (a synthetic analog of prostaglandin F2α; PGF), simultaneously with the P4 implant removal. On d 0, the protocol for synchronization of ovulation was initiated with 16.8 µg of buserelin acetate (a synthetic analog of GnRH) and insertion of a 2.0 g P4 implant, followed by a treatment with 0.530 mg of PGF on d 6, and a second PGF on d 7, concomitant with the P4 implant withdrawal. In Group EC, cows received 1.0 mg of EC on d 7 as an ovulation inducer. In G group, cows received 8.4 µg of GnRH 56 h after the first PGF (16 h before TAI). In Group EC/G, cows received both EC and GnRH. The TAI was performed on d 9 (48 h after P4 withdrawal) in all experimental treatments. There were no differences among treatments on pregnancy per AI (P/AI) on d 31 (40.4%; 367/909). There was a tendency for greater pregnancy loss in G group (19.8%) than in EC (12.2%) and EC/G (10.1%) groups. When the 2 groups that received EC were combined, the pregnancy loss was lower than when cows received only GnRH (11.2% [21/188] vs. 19.8% [17/86]; P = 0.05). There was an interaction between treatment and expression of estrus on P/AI, in which estrus positively affected P/AI in EC (53.3% vs. 20.0%) and EC/G (53.1% vs. 36.7%), but not in G group (41.5% vs. 38.7%). Overall, 81% of the cows had a corpus luteum (CL) on d 0 and 91% at PGF treatment of the breeding protocols. Fertility was greater in cows with CL at the time of the first PGF treatment than in cows without CL (45.9% vs. 17.7%). In summary, the strategies to induce final ovulation resulted in similar fertility despite the different physiological responses, such as expression of estrus, but further research is needed to definitively confirm the relationship between lack of EC and increased pregnancy loss.